BEST PRACTICE SCHOOLS IN FUNDRAISING FOR EDUCATION IN BASIC SCHOOL MINISTRY OF EDUCATION OF SCHOOLS - Pophan, Pornthep; Chansirisira, Pacharawit; Pumipuntu, Chaloey (Journal of Buddhist Anthropology, 2020)
The purposes of this research were to study current condition of the school in fundraising for education. And To study best practices schools in fundraising. This research integrated Mix-method. The research study was divided into 2 phases as follows: Phase 1: were study current condition of the school in fundraising for education. The research integrated quantitative research methods. The samples used in the study were drawn from multi-stage random sampling. There are 378 schools under the Office of the Basic Education Commission, consisting of the school administrators, teachers involved in fundraising and chairmen of basic education committees from 1,134 sample. The instrument used as a questionnaire with a discrimination between 0.228 – 0.876 reliability of 0.985. The data analysis included the Mean and Standard Deviation. Phase 2: were study best practices schools for fundraising. The research integrated quantitative research methods. The target group is a school that is successful in raising funds. Primary level 1 school and secondary school amount 1 school. The research instruments used were survey data, observation questionnaire, analytical interview, the research findings revealed that: Current condition of the school in education funding at the highest level ( = 3.53, S.D. = 0.65), fundraising knowledge for education that needs training at the highest level ( = 3.97, S.D. = 0.53). And best practices in successful schools for fundraising. It has been found that the fundraising for primary schools’ element of a successful fundraising institution will require 3 steps, 18 elements and secondary element of a successful fundraising institution will require 3 steps, 20 elements.